2021
DOI: 10.2340/16501977-2824
|View full text |Cite
|
Sign up to set email alerts
|

Drop-out from chronic pain treatment programmes: Is randomization justified in biopsychosocial approaches?

Abstract: Objective To identify profiles of patients who are at risk of dropping out from biopsychosocial approaches to chronic pain management. Patients A total of 575 patients were included in the study. Of these, 203 were randomized into 4 treatment groups: self-hypnosis/self-care; music/self-care; self-care; and psychoeducation/cognitive behavioural therapy. The remaining 372 patients were not randomized, as they presented with the demand to learn self-hypnosis/self-care, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Standardisation of the techniques did not allow an adaptation to the patient situation. 37 In our study, we used one design of ‘passive VR’ with no interactions and no user's control of the environment. Users’ interactions with the virtual reality environment and possibility of action (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Standardisation of the techniques did not allow an adaptation to the patient situation. 37 In our study, we used one design of ‘passive VR’ with no interactions and no user's control of the environment. Users’ interactions with the virtual reality environment and possibility of action (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, applying the ITT technique rendered our analyses robust but could not reveal a group effect because too many patients maintained the same score (sometimes the T1 score) over the 4 time points. Furthermore, in another study [58] we demonstrated that the delayed onset of treatments (� 4 months) and randomization significantly increased the risk of never starting the treatments. These results urged us to rethink the accuracy of only relying on randomized control trials to evaluate the effectiveness of complementary approaches.…”
Section: Plos Onementioning
confidence: 82%
“…This preference-based design was chosen because we did not find it relevant for a patient who wants to participate, for example, in the hypnosis intervention to be obliged to participate in another intervention. Indeed, patients who can chose their treatment have more motivation and a greater adherence ( King et al, 2005 ; Preference Collaborative Review Group, 2008 ; Sedgwick, 2013 ; Bicego et al, 2021a ). We also chose this design based on our clinical observations.…”
Section: Discussionmentioning
confidence: 99%
“…We designed a longitudinal controlled superiority trial (see Figure 1 ) with 160 patients with cancer who will choose between four conditions (see section “Recruitment” for sample size calculation): hypnosis-based group intervention, MSC meditation-based group intervention, SICT-based group intervention, or a control group. This kind of design has been chosen because patients who receive their preferred therapeutic option seem to be more motivated and exhibit greater adherence to the treatment ( King et al, 2005 ; Preference Collaborative Review Group, 2008 ; Sedgwick, 2013 ; Bicego et al, 2021a ). Indeed, preference-based trials are increasingly developed as researchers often want to know if an intervention is effective for the participants who choose it, rather than determining the best treatment option irrespective of the participant’s choice ( Kowalski and Mrdjenovich, 2013 ).…”
Section: Methods and Analysismentioning
confidence: 99%